Endovascular treatment of giant and large intracranial aneurysms by using a combination of stent placement and liquid polymer injection - Mawad, Michel E. (2002)
Mawad, M. E., Cekirge, S., Ciceri, E., & Saatci, I. (2002). Endovascular treatment of giant and large intracranial aneurysms by using a combination of stent placement and liquid polymer injection. Journal of neurosurgery, 96(3), 474-482.